THE ROLE OF LEADERSHIP FROM THE PERSPECTIVE OF INTRA ORGANIZATIONAL COMMUNICATIONS AT THE CENTRAL STATISTICS AGENCY OF PALU CITY - Mariyani, Ince; Thahir, Harifuddin; Adda, Harnida Wahyu (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This research aims to find out the role of leadership from the perspective of intra-organizational communication at the Central Statistics Agency of Palu City. This research used a qualitative research method, to find out the facts and phenomena that occur regarding the leadership role from an intra-organizational perspective at the Central Statistics Agency of Palu City. The analysis consists of three stages, namely : data reduction, data presentation, and concluding. The results of the research show that 1) openness, there is a very visible difference in the form of communication carried out by superiors to subordinates (section heads) with employees as the lowest ranks in the organizational level. 2) Empathy, the head of the Central Statistics Agency of Palu City has a high sense of empathy for the problems and work needs of his subordinates, and the situation is not conducive in the environment of the Central Statistics Agency of Palu City. However, for personal interests, the attitude of empathy from the leadership is still lacking. Support, the head of the Central Statistics Agency of Palu City has not fully provided support to subordinates while the support for the fulfillment of facilities and infrastructure is good. 3) Positivity, the work is given by the head of the Central Statistics Agency of Palu City to its employees is responded to with a positive attitude so the positive indicators at the Central Statistics Agency of Palu City are good. 4) Similarity, perception in work which is one of the keys to the success of employees, has been carried out well. Keywords: Leadership Role, Intra-Organizational Communication